The degree of commitment of secondary school principals to the teaching ethics from the point of view of their teachers - Alkhalidi, Mariam (Dirasat: Educational Sciences, 2020)
This study aimed to identify the degree of commitment of secondary school principals to the ethics of the teaching profession from the point of view of their teachers. The study sample consisted of (80) members selected randomly, and to achieve this goal, the researcher used the descriptive survey method. The results of the study showed that the degree of commitment of secondary school principals to the ethics of the teaching profession from the point of view of their teachers and for the various fields, came with an average rating, where the field of ethics towards students in the first place, followed by the field of ethics of the Director towards the parents of students and the local community in the second place, and followed by the field of ethics ethics towards teachers in the third place. The results showed that there are no statistically significant differences attributed to the variable years of experience in the areas of practicing the ethics of the profession towards (teachers, students, parents and the community). The study made several recommendations in the light of these results of increasing the awareness of school administrators. The importance of ethical leadership through workshops and courses because of this critical importance for both school principals, teachers, students and educational learning process.